Kinetic and Equilibrium Studies on the Exchange Process of n-Hexanol and Cetyl Trimethyl Ammonium Bromide (CTAB) Micelles - Wan Badhi, Wan Ahmad; Suhaimi, Hamdan; Ibrahim, Ramli; Hassan, Senin (Universiti Putra Malaysia Press, 1995)
Kinetic studies using ultrasonic relaxation method in the mixed micellar solutions of n-hexanol dan cetyl trimethyl ammonium bromide have shown a well-defined single relaxation. This is associated with the exchange process involving the partitioning of alcohol with the mixed micelle. The equilibrium measurement which monitors the monomer concentration of n-hexanol was measured using head space analysis involving gas chromatography. The combined relaxation and equilibrium data were analysed using a phenomenological treatment in which the kinetics and thermodynamics parameters were evaluated for the exchange process. The main conclusion from this work is that the association of n-hexanol to the the mixed micelles is almost a diffusion controlled process.